2018
DOI: 10.1007/s11524-018-0266-2
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood and Network Characteristics and the HIV Care Continuum among Gay, Bisexual, and Other Men Who Have Sex with Men

Abstract: In order for treatment as prevention to work as a national strategy to contain the HIV/AIDS epidemic in the United States (US), the HIV care continuum must become more robust, retaining more individuals at each step. The majority of people living with HIV/AIDS (PLWHA) in the US are gay, bisexual, and other men who have sex with men (MSM). Within this population, there are distinct race- and ethnicity-based disparities in rates of HIV infection, engagement, and retention in HIV care, and viral suppression. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 188 publications
0
14
0
Order By: Relevance
“…Theoretical and empirical work suggests that such high HIV prevalence among these vulnerable populations is not driven by factors at individual level, as black MSM, for example, are often no more likely to engage in behaviors that increase risk of HIV infection (e.g., using drugs during sex, condomless anal intercourse) [3,4]. Rather, the racial disparity in HIV incidence is produced and perpetuated by more distal factors, including the characteristics of networks and neighborhood environments [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and empirical work suggests that such high HIV prevalence among these vulnerable populations is not driven by factors at individual level, as black MSM, for example, are often no more likely to engage in behaviors that increase risk of HIV infection (e.g., using drugs during sex, condomless anal intercourse) [3,4]. Rather, the racial disparity in HIV incidence is produced and perpetuated by more distal factors, including the characteristics of networks and neighborhood environments [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Individual-level adverse health outcomes may be influenced directly or indirectly by the environment where a person lives [8][9][10]. Gay neighborhoods have been associated with HIV infection [11,12], although there is some debate over whether living in a gay neighborhood is a risk factor or protective factor.…”
Section: Introductionmentioning
confidence: 99%
“…Gay neighborhoods have been associated with HIV infection [11,12], although there is some debate over whether living in a gay neighborhood is a risk factor or protective factor. Tieu et al [9] associated living in a gay neighborhood with safer sex behaviors such as more frequent condom use for receptive and insertive anal sex. This agrees with the fact that individuals who perceive a higher sense of community and neighborhood participation are more likely to report fewer risk behaviors [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This special issue opens with three articles that focus on understanding how social/structural forces operating in local ecological contexts influence HIV. Tieu et al [5] offer potential pathways by which neighborhood-and network-level factors affect the HIV care continuum for Black MSM while Cassels et al [6] identified place-related patterns that influenced HIV vulnerability and access to health care among substance-using Black MSM in Los Angeles. Hotton et al [7] investigated neighborhood-level and socio-structural predictors of criminal justice involvement among MSM in Chicago, which is a particularly salient topic given how the over-policing and criminalization of Black communities hasled to large proportions of Black men being exposed to the criminal justice system.…”
mentioning
confidence: 99%